Modulatory effects of Aroclors 1221 and 1254 on bone turnover and vertebral histology in intact and ovariectomized rats - Yilmaz, Bayram; Seyran, Ayse D.; Sandal, Suleyman; Aydin, Mehmet; Colakoglu, Neriman; Kocer, Muzaffer; Carpenter, David O. (Elsevier Ireland Ltd, 2006)
Polychlorinated biphenyls (PCBs) are persistent environmental pollutants. Two PCB mixtures, Aroclors 1221 and 1254 have been suggested to have estrogenic and anti-estrogenic properties, respectively. We have examined whether these PCB mixtures modulate bone turnover and vertebral histology in intact and ovariectornized (ovx) rat models. Thirty-two adult female rats were divided into four groups subcutaneously receiving 4% DMSO (control), A1221 (10mg/kg), A1254 (10mg/kg) oestradiol (E-2, 30 mu g/kg). These compounds were injected to the animals for a period of 6 weeks at two daily intervals. In the second model, rats (n = 32) were ovx and allowed to recover for a period of 3 weeks. Control group received vehicle (4% DMSO) alone. Remaining rats were divided into three groups and injected (s.c.) with A1221, A1254 and E2 for 5 weeks. Urine samples were collected prior to end of the experiments. Then, all animals were decapitated. Serum parathyroid hormone (PTH), calcitonin and osteocalcin levels were determined by immunoradiometric method. Serum concentrations of alkaline phosphatase (ALP), calcium and inorganic phosphate were determined by enzymatic-colorimetric method. Urinary deoxypyridinoline (DPD) was measured by ELISA. Lumbar vertebrae (1-2) of all animals were dissected out and processed for light microscopy. Levels of urinary DPD were significantly lowered in E-2-treated intact rats (p < 0.001). Ovx significantly increased urinary DPD excretion (P < 0.01) compared to intact control values. Administration of A 1221 and A 1254 had no significant effects in intact rats, however, they significantly reduced (p < 0.05) and increased (p < 0.001) urinary DPD levels in ovx rats, respectively. Neither of the PCB mixtures significantly changed serum osteocalcin and ALP levels in intact or ovx rats (except A1221 increased ALP in intact model, p < 0.01). Both PCB mixtures had differential effects on serum PTH, calcitonin, calcium and inorganic phosphate concentrations. Treatment with A1221 reversed the adverse effects of ovariectomy on L2 histology. However, A1254 produced necrotic areas in vertebral bone, and this effect was expanded in ovx animals. Our findings suggest that both Aroclor compounds interfere with bone turnover mechanisms, particularly in ovx rats. (c) 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: bone turnover; endocrine disruption; PCB; Aroclors 1221 and 1254